Симон - Хейлер - Келдыш Юрий Всеволодович (Энциклопедии. Словари. Справочники, 1981)
Экземпляры: ИСК (20120718) / Инвентарный номер: 738006 / Сис.шифр: 85.31 / Авт.знак: М 89 / ГРНТИ: 18 / ББК: 85.31я2